Urgensi Layanan Konseling untuk Anak Usia Dini: Dalam Mengidentifikasi Kebutuhan Kesehatan Mental pada Anak Usia Dini - Hafidz Awlawi, Addahri; Ifnaldi (Malewa: Journal of Multidisciplinary Educational Research, 2024)
Early childhood mental health has a significant impact on their emotional, social and cognitive development, making it a critical component of their overall development. Despite this, early childhood therapy services are often overlooked or considered unimportant. By analysing the frequency of mental health problems, the advantages of early intervention, and the benefits of counselling in promoting healthy development, this research article seeks to emphasise the critical need for offering counselling services to young children. This article highlights the need for accessible and developmentally appropriate counselling services to enhance children's well-being through a thorough assessment of literature, case studies, and analysis of contemporary practices.